Remarkable repellency of Ligusticum sinense (Umbelliferae), a herbal alternative against laboratory populations of Anopheles minimus and Aedes aegypti (Diptera: Culicidae) - Rukpong Sanghong (2018)
© 2015 Sanghong et al. Abstract Background: For personal protection against mosquito bites, user-friendly natural repellents, particularly from plant origin, are considered as a potential alternative to applications currently based on synthetics such as DEET, the standard chemical repellent. This study was carried out in Thailand to evaluate the repellency of Ligusticum sinense hexane extract (LHE) against laboratory Anopheles minimus and Aedes aegypti, the primary vectors of malaria and dengue fever, respectively. Methods: Repellent testing of 25% LHE against the two target mosquitoes; An. minimus and Ae. aegypti, was performed and compared to the standard repellent, DEET, with the assistance of six human volunteers of either sex under laboratory conditions. The physical and biological stability of LHE also was determined after keeping it in conditions that varied in temperature and storage time. Finally, LHE was analysed chemically using the qualitative GC/MS technique in order to demonstrate a profile of chemical constituents. Results: Ethanol preparations of LHE, with and without 5% vanillin, demonstrated a remarkably effective performance when compared to DEET in repelling both An. minimus and Ae. aegypti. While 25% LHE alone provided median complete-protection times against An. minimus and Ae. aegypti of 11.5 (9.0-14.0) hours and 6.5 (5.5-9.5) hours, respectively, the addition of 5% vanillin increased those times to 12.5 (9.0-16.0) hours and 11.0 (7.0-13.5) hours, respectively. Correspondingly, vanillin added to 25% DEET also extended the protection times from 11.5 (10.5-15.0) hours to 14.25 (11.0-18.0) hours and 8.0 (5.0-9.5) hours to 8.75 (7.5-11.0) hours against An. minimus and Ae. aegypti, respectively. No local skin reaction such as rash, swelling or irritation was observed during the study period. Although LHE samples kept at ambient temperature (21-35°C), and 45°C for 1, 2 and 3 months, demonstrated similar physical characteristics, such as similar viscosity and a pleasant odour, to those that were fresh and stored at 4°C, their colour changed from light- to dark-brown. Interestingly, repellency against Ae. aegypti of stored LHE was presented for a period of at least 3 months, with insignificantly varied efficacy. Chemical analysis revealed that the main components of LHE were 3-N-butylphthalide (31.46%), 2, 5-dimethylpyridine (21.94%) and linoleic acid (16.41%), constituting 69.81% of all the extract composition. Conclusions: LHE with proven repellent efficacy, no side effects on the skin, and a rather stable state when kept in varied conditions is considered to be a potential candidate for developing a new natural alternative to DEET, or an additional weapon for integrated vector control when used together with other chemicals/measures.